Schizophrenia and Sex Hormones: What Is the Link? - Brzezinski-Sinai, Noa A.; Brzezinski, Amnon (Frontiers in Psychiatry, 2020)
The involvement of gonadal hormones in the pathogenesis of schizophrenia has long been suspected because the psychosis differs in women and men and the illness first makes its appearance shortly after puberty. Fluctuations in estrogen and progesterone have been linked with increased vulnerability to mood disorders in women, while elevated levels of testosterone have been primarily associated with increased sexual drive and aggressiveness in both men and women. Some studies have found abnormal levels of estrogens and testosterone in schizophrenia patients, but the results have been equivocal and sometimes attributed to the antipsychotic-induced hyperprolactinemia, which may alter levels of gonadal hormones. The purpose of this review is to present the current knowledge on the link between fluctuations of sex-hormones in women and the course of schizophrenia, and to optimize the approach to women with schizophrenia during the various stages of the female reproductive life (i.e. puberty, menstrual cycle, pregnancy, contraception and menopause).